HUBUNGAN KEMISKINAN DAN PRODUK DOMESTIK REGIONAL BRUTO DALAM UPAYA MENINGKATKAN INDEKS PEMBAGUNAN MANUSIA DI KABUPATEN BOJONEGORO TAHUN 2015-2019 - Edy Suhartono (JURNAL ILMIAH EDUNOMIKA, 2022)
The purpose of this study was to determine the effect of poverty and Gross Regional Domestic Product partially on the Human Development Index (HDI) in Bojonegoro Regency in 2015-2019; to determine the effect of poverty and Gross Regional Domestic Product simultaneously on the Human Development Index (IPM) in Bojonegoro Regency in 2015-2019; and to find out the dominant variables affecting the Human Development Index (HDI) in Bojonegoro Regency in 2015-2019. The data used in this study is secondary data obtained from the Central Statistics Agency (BPS). The method used is multiple linear regression using time series data and the analysis technique used is the Ordinary Least Square (OLS) model. In processing the data, the author uses Eviews 10 software. The results of the analysis in this study are the Poverty variable has a significant negative effect on the Human Development Index in Bojonegoro Regency and the Gross Regional Domestic Product variable has a positive and insignificant effect on the Human Development Index in Bojonegoro Regency. The dominant variable affecting the Human Development Index in Bojonegoro district is poverty.